A participatory approach to preventing hospital nurses’ psycho-social stress - Bär, Stefan; Starystach, Sebastian (The Social Publishers Foundation, 2018)
identify and initiate necessary structural changes in the work of nurses at a German University Clinic. Based on the mental stress that nursing staff demonstrated in the results from a survey data, preventive measures in the context of a risk assessment of psycho-social stress was implemented. participatory research